Cell-free DNA in pregnancy with choriocarcinoma and coexistent live fetus: A case report. Issue 37 (September 2016) - Kristiansen, Mona Kjaerboel; Niemann, Isa; Lindegaard, Jacob Christian; Christiansen, Mette; Joergensen, Mette Warming; Vogel, Ida; Lildballe, Dorte Launholt; Sunde, Lone
Abstract: Background: This case report describes the use of analysis of cell-free DNA in the blood of a patient with a pregnancy with one live fetus and a choriocarcinoma diagnosed at 22 weeks of gestation. Results: The result of the analysis of 16 microsatellite loci on 14 chromosomes in the cell-free DNA in plasma was consistent with the result of the analysis of a tumor biopsy indicating biparental diploid origin of the genome. The DNA markers were discordant with the markers of the placenta indicating two separate conceptions. Conclusion: Our results indicate that analysis of cell-free DNA in plasma allows determination of the origin of a choriocarcinoma without tissue biopsy, even in the presence of a co-existent pregnancy.